Utilization of the Microbiome to Increase Food Security Throught Sustainable Biotechnology - Hazmi, Muhammad; Jiwon, Seo; Kingh, Ruby (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Food security remains a critical global challenge, requiring innovative and sustainable solutions to meet the growing demand for nutritious food. One promising approach is the utilization of microbiomes in sustainable biotechnology to enhance agricultural productivity, improve soil health, and increase food production efficiency. This study aims to explore the potential of microbiome-based biotechnological applications in strengthening food security through sustainable agricultural practices. A qualitative research methodology was employed, involving an extensive literature review and analysis of case studies related to microbiome utilization in agriculture. The findings indicate that microbiomes play a significant role in improving crop resilience, enhancing nutrient absorption, and reducing the need for chemical fertilizers and pesticides. Furthermore, microbiome-based biotechnology contributes to environmental sustainability by promoting soil biodiversity and reducing greenhouse gas emissions. The study concludes that integrating microbiome technology into agricultural systems can significantly enhance food security while ensuring ecological balance. Future research should focus on optimizing microbiome applications and developing scalable implementation strategies for various agricultural settings.